First Impressions of the Soviet Occupation of 1940 with the US Lithuanians: The Stories of Photographer Kazys Lukšys - Skirius, Juozas (History / Istorija, 2024)
Abstract. Very limited information about the first Soviet occupation of Lithuania in 1940–1941 and its aftermath reached the foreign public, including the Lithuanian diaspora. The leaders of the Lithuanian diaspora and Lithuanian diplomats abroad gathered even the slightest information about the effects of the Sovietization on the country from a wide variety of sources (the foreign press, foreign diplomats, and the stories of people who had fled Lithuania). This information was essential for informing the world about the real situation in the occupied country. One of the first such “living sources” was the famous Lithuanian photographer and film-maker Kazys Lukšys (1892-1963), who arrived from Lithuania in March 1941 in Los Angeles (USA). During his conversation with the Lithuanian consul, Julius J. Bielskis, the latter gathered his impressions of the situation in Soviet-occupied Lithuania, the radical transformations in all spheres of the country’s life, and the pillaging and destruction of the country. The consul sent all this information, summarized in a letter dated 30th March, 1941, to the Lithuanian envoy Povilas Žadeikis in Washington. J. J. Bielskis himself kept a copy of the letter in the consulate archives.